AGROCHEMICAL ASSESSMENT OF THE IMPACT OF MINERAL FERTILIZERS AND FOLIAR FERTILIZATION ON THE YIELD OF SPRING BARLEY IN THE WESTERN FOREST-STEPPE - Veha Н. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The article presents findings of research on the influence of various norms of mineral fertilizers and foliar application of micro element fertilizer on the change of spring barley productivity on dark-gray podzolic soil of the Western Forest-Steppe. The research was accompanied by a two-factor field experiment. Factor A provided for the application of different rates of mineral fertilizers: 1) without fertilizers (control); 2) N30P30K30; 3) N45P45K45; 4) N60P60K60. According to the scheme of the experiment, Factor B included options for foliar fertilization of crops: 1) spraying with water; 2) Vitazim, 1.0 l/ha. Mineral fertilizers were applied in the form of nitroammophoska for cultivation. Foliar application of Vitazym fertilizer was carried out in the tillering phase of spring barley. The high efficiency of mineral fertilizers and foliar fertilization of Vitazym microelement fertilizer in increasing the yield of spring barley has been established. On the background of appluing mineral fertilizers in the norm of N30P30K30 and N45P45K45 and spraying with water, the grain yield was obtained at the level of 4.54 and 5.09 t/ha respectively. The excess of the option without fertilizers was 0.41 and 0.96 t/ha. In the variant of the application norm of mineral fertilizers N60P60K60 the indicator was higher and amounted to 5.39 t/ha. Foliar fertilization of spring barley crops with Vitazym fertilizer on the background of mineral fertilizers in the norm N30P30K30 provided an increase in yield of 0.13 t/ha comparing to the variant of mineral fertilizers, N45P45K45 – 0.21 t/ha. The yield level was 4.68 and 5.30 t/ha respectively. The highest rate was obtained under fertilization on the background of fertilizer in the norm N60P60K60, where it was 5.62 t/ha, which exceeded the option without fertilization by 0.23 t/ha. As a result of regression analysis, a close correlation was established between the yield of spring barley and the norms of mineral fertilizers application on dark gray podzolic soil. The coefficient of determination R2 is 0.96. The dependence of spring barley yield increases under foliar fertilization of crops with microelement fertilizer Vitazym on a mineral background on the norms of mineral fertilizers was established. The coefficient of determination, characterizing the closed connection, was at the level of 0.92, confirming close relationship between the features.